Conservation of geosites as a tool to protect geoheritage: the inventory of Ceará Central Domain, Borborema Province - NE/Brazil - Moura, Pâmella (2017)
The Ceará Central Domain, in the northern Borborema Province/NE Brazil, encompasses important geological records (geosites) which allow understanding a relevant period of the Earth’s evolution, mainly associated to Neoproterozoic Brazilian/Pan-African Cycle and West Gondwana amalgamation, besides Neoarchean to Ordovician records. The presented geoheritage inventory aims to characterise the geosites with scienti c relevance of Ceará Central Domain. By applying a method for large areas, the nal selection resulted in eight geological frameworks represented by 52 geosites documented in a single database. This is the rst step for a geoconservation strategy based on systematic inventories, statutory protection, geoethical behaviour and awareness about scienti c, educational and/or cultural relevance of geosites.